Refining ku-band rain attenuation prediction using local parameters in tropics - Yaccop, Afham Abd Hakim; Yao, Yudong; Ismail, Ahmad Fadzil; Badron, Khairayu; Hasan, Mohammad Kamrul (Indian Society for Education and Environment, 2016)
Background/Objectives: Researches disclosed rain attenuation prediction models offered by ITU-R severely underestimate the signal attenuation in tropical region. Improvement can be accomplished by incorporating three in-situ parameters of prediction models. Methods/Statistical Analysis: The locally derived components are rainfall rate, rain height and specific attenuation coefficients. Beacon signal data for MEASAT-I satellite were sampled for one year. Sampling time of 1 minute was chosen for rainfall rate. Both attenuation and rainfall rate were represented in terms of annual cumulative distribution. Rain height data were gathered from related researches and visually compared with radar data of 10 convective and 30 stratiform rain events. Findings: In previous works, these components were treated separately. By combining all three components, rain attenuation prediction model with distinctive accuracy can be acquired compared to the previous results. All previous and current works exhibited significant improvement from the latest ITU-R P.618 revision 12 model. The new result closely fitted in with measured attenuation which was not present in any previous work. This was shown by RMS error of 2.02 dB at availability of 99.9% to 99.999% (0.1% to 0.001% exceedance). Application/Improvements: Accurate representation of fade margin can be included in link budget analysis by designers for satellite deployment in tropical region.